SME’s insurance through banking channel - M. .. Manchurak (Путеводитель предпринимателя)
Small business insurance in Russia developed insufficiently, which is a definite reflection of the lack of development lending to this segment of consumers. The article presents the author’s practical techniques to increase the volume of premiums in this segment of the insurance market.